(untitled) (MMIT Proceedings, 2026)
This article examines the economic opportunities, regulatory gaps, and food safety challenges faced by alternative and home-based food entrepreneurs operating through digital food marketplaces in Uzbekistan, and explores pathways for their sustainable development. The study employs a qualitative research methodology, including in-depth interviews with 35 micro-entrepreneurs active on two distinct platform types, alongside analysis of platform operational data and content review of regulatory frameworks. Findings indicate that traditional registration and sanitary-epidemiological requirements constitute a high entry barrier for non-traditional vendors, compelling 68% to operate informally. Conversely, it was determined that digital platform trade increases average revenues by 34%, reduces operational costs by 29%, and expands employment opportunities for women and rural populations by 41%. The paper proposes a phased formalisation model for platform-driven food businesses and develops actionable recommendations for entrepreneurs, regulatory authorities, and platform operators. The research findings hold significant implications for advancing Uzbekistan’s digital economy strategy, integrating the informal sector, and preserving national culinary heritage within digital ecosystems.